2013
DOI: 10.1007/s00280-013-2360-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of sunitinib and SU12662 on dermatological toxicities in metastatic renal cell carcinoma patients: in vitro, in vivo, and outcomes investigation

Abstract: Sunitinib may be more dermatotoxic than SU12662 from both in vivo and in vitro evidences. Therefore, appropriate management of DTs may be essential, especially in patients with a reduced sunitinib metabolising ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Both sunitinib and SU12662 act on similar receptors, such as VEGFR, PDGFR and KIT, and the toxic effects associated with sunitinib therapy could also probably be attributed to SU12662. Sunitinib has been shown to be more toxic than SU12662 in keratinocytes [11], but the differential toxicity of sunitinib and SU12662 in other cell types has not yet been specified. Previous studies reported a correlation with oral adverse events, such as mucositis and HFSR [22].…”
Section: Discussionmentioning
confidence: 99%
“…Both sunitinib and SU12662 act on similar receptors, such as VEGFR, PDGFR and KIT, and the toxic effects associated with sunitinib therapy could also probably be attributed to SU12662. Sunitinib has been shown to be more toxic than SU12662 in keratinocytes [11], but the differential toxicity of sunitinib and SU12662 in other cell types has not yet been specified. Previous studies reported a correlation with oral adverse events, such as mucositis and HFSR [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the genetic variant rs776746 G > A in the drug-metabolizing enzyme CYP3A5 is associated with the defective CYP3A5 expression, resulting in a decreased conversion of sunitinib into SU12662. It has been reported that sunitinib exhibited more dermatological toxicities (among which hand-foot syndrome) compared to SU12662 [53]. Garcia-Donas et al reported the association of CYP3A5 Ã 3 with toxicity-related dose reduction in 101 Spanish mRCC patients [54].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen articles (Table I) identifying six instruments (Table II) met the inclusion criteria. Four instruments were generic (Skindex-16© [2,9–11], Skindex-29© [12], Dermatology Life Quality Index [DLQI] [6,13], Deutsches Instrument zur Erfassung der Lebensqualität bei Hauterkrankungen [DIELH-24] [14]) and two were symptom-specific Functional Assessment of Cancer Therapy-Epidermal Growth Factor Receptor Inhibitors-18 [FACT-EGFRI-18] [15,16] and Hand-Foot Syndrome 14 [HFS-14][1719]).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the investigators evaluated the differences in plasma sunitinib and metabolite concentrations between patients with and without dAEs. [19] In this study, hand and feet complaints were assessed utilizing HFS-14. This demonstrates another utility of PRO instruments: to correlate clinical outcomes with biochemical findings.…”
Section: Discussionmentioning
confidence: 99%